Dermatoglyphic analysis of fingers, palms and soles prints of population from Giebło village (district Zawiercie) - Gralla , Gertruda (Anthropological Review, 1975)
The author has investigated dermatoglyphic patterns among 485 inhabitants (236 males and 249 females) of the Giebło village. From this material 202 unrelated individuals (103 males and 99 females) were choosen for further analysis as representatives of kinship groups. Finger patterns (table 1 - 4), lines DCBA terminations (table 5 - 6), patterns on palms (table 7 - 9) and soles (table 10 - 13) surfaces were considered separately. Frequencies of particular finger patterns, as well as other dermatoglyphic features in investigated population, differ considerably from averages for Poland. The author suggests that this property of some populations ought to be taken into consideration in paternity affiliation.